Fungsi Aizuchi Sebagai Strategi Kesantunan Dalam Anime “Apothecary Diaries” Season 1 Karya Natsu Hyuga - Cahya Aura Prameshwari; Putu Dewi Merlyna Yuda Pramesti; I Wayan Sadyana (Global Education Journal, 2026)
In Japanese communication, aizuchi plays an important role in maintaining interaction and expressing attentiveness toward the speaker. Although aizuchi has been widely studied as a listener response, its role as a politeness strategy in fictional conversations remains underexplored. This study aims to analyze the forms, types, and functions of aizuchi that reflect politeness strategies in the anime "Apothecary Diaries" Season 1 episodes 1-6. The method used is a qualitative descriptive method with a pragmatic approach. The research data are dialogues containing aizuchi classified based on the types and functions of aizuchi according to Horiguchi (1997) and politeness strategies according to the theory of Brown and Levinson (1987). The results show that there are 33 aizuchi utterances that reflect politeness strategies. The most frequently used politeness strategy is Positive Politeness (18 data), followed by Negative Politeness (11 data), Bald on Record (2 data), and Off-Record (2 data). In terms of function, aizuchi is most often used as a sign of understanding (16 data) and confirming information conveyed by the interlocutor (9 data). Thus, the use of aizuchi in the anime “Apothecary Diaries” is able to reflect politeness that considers social hierarchy, emotional closeness, and the context of the conversation.